2019
DOI: 10.1186/s12913-019-4566-3
|View full text |Cite
|
Sign up to set email alerts
|

Access to public health services and integral care for women during the puerperal gravid period period in Ceará, Brazil

Abstract: BackgroundOver time, the Brazilian health system, a growing country, has been developing to ensure good accessibility to health goods and services. This development is focusing on the principle of universality of access and completeness of health care. In this context, we aimed to evaluate the completeness of care and universality of access for women in their pregnancy and puerperal period in Ceará, Brazil.MethodsA descriptive, cross-sectional study based on a quantitative approach, using information collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
0
13
0
15
Order By: Relevance
“…11 However, the index found is within the rate pointed out in a literature review study that found adherence rates ranging from 16.8 to 58%. 6,27 This index is far below the desired one, when compared to the data of the United Kingdom, where adherence to the puerperal consultation shows an index of 91%. 27 Low adherence can directly reflect on problems and complications that may arise in the puerperium and turn a routine appointment into a need for emergency care.…”
Section: Coefficientmentioning
confidence: 68%
See 1 more Smart Citation
“…11 However, the index found is within the rate pointed out in a literature review study that found adherence rates ranging from 16.8 to 58%. 6,27 This index is far below the desired one, when compared to the data of the United Kingdom, where adherence to the puerperal consultation shows an index of 91%. 27 Low adherence can directly reflect on problems and complications that may arise in the puerperium and turn a routine appointment into a need for emergency care.…”
Section: Coefficientmentioning
confidence: 68%
“…5 The puerperal consultation consolidates assistance to the pregnancypuerperal cycle, in completeness and quality, consisting of an important care indicator. 6 Carrying out the puerperal return is one of the nurse's duties in Primary Health Care and, if lack of postpartum is detected, an active search should be carried out. However, it is noted that there is no standardization in the conduct and that the commitment to carry it out is different.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing rates of maternal syphilis over the past decade are likely multi-factorial. Increased syphilis testing and enhanced surveillance as part of the Rede Cegonha and Projeto Nascer campaigns, public policy initiatives aimed at improving prenatal care in Brazil, are possible explanations for increased identification of maternal and congenital syphilis cases throughout the country [ 15 ]. While prenatal care is accessible to all pregnant women under the SUS network in Brazil, the quality may be suboptimal, particularly among women of a lower socioeconomic status [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014, a total of 11 countries received WHO validation for dual elimination of HIV and syphilis MTCT [ 14 ]. In response to the PAHO goal of dual elimination, several public policies were implemented in Brazil to increase testing capacity and treatment [ 15 ]. Despite these efforts, rates of maternal and congenital syphilis continue to climb in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…And, when one evaluated the right of universality in the access of women during pregnancy and the puerperium it was found that the federal policy on maternal and child health has weaknesses in access to care for women in prenatal care, childbirth and the puerperium, therefore a study recommended that managers prioritize actions to improve this policy to guarantee access to health of the binomial (20) . Similar results were found in researches that showed that women who received information on pregnancy and childbirth were significantly more likely to know any danger signs, compared to women who did not receive information (21) ; and identified a low level of women's knowledge about obstetric danger signs during pregnancy, childbirth and postpartum, finding that women who were unaware were more susceptible to delay in deciding to seek care.…”
Section: A Survey That Evaluated 3 Delays Model In Amentioning
confidence: 99%